2022
DOI: 10.1111/acv.12816
|View full text |Cite
|
Sign up to set email alerts
|

Not just the Big Five: African ecotourists prefer parks brimming with bird diversity

Abstract: Ecotourism helps sustain protected areas (PAs) that in turn conserve Africa's declining fauna. Identifying ecotourist preferences and which species and landscapes benefit from ecotourism could therefore support African biodiversity conservation efforts. Due to historic associations with trophy hunting and subsequent ecotourism marketing efforts, ecotourist preferences have been thought to traditionally center around the ‘Big Five’: elephant, lion, buffalo, leopard, and rhinoceros. But these preferences may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Ecotourism has increasingly been recognized as an important source of revenue for protected areas as well as their surrounding communities (Hausmann et al ., 2016; Eyster, Naidoo, & Chan, 2022; Gupta et al ., 2023). Particularly in southern and eastern Africa, ecotourism is linked with charismatic species ‐ the Big Five‐, i.e., African elephant ( Loxodonta africana ), rhinoceros ( Diceros bicornis , Ceratotherius simum ), lion ( Panthera leo ), African buffalo ( Syncerus caffer ), and leopard ( Panthera pardus ).…”
Section: Figurementioning
confidence: 99%
“…Ecotourism has increasingly been recognized as an important source of revenue for protected areas as well as their surrounding communities (Hausmann et al ., 2016; Eyster, Naidoo, & Chan, 2022; Gupta et al ., 2023). Particularly in southern and eastern Africa, ecotourism is linked with charismatic species ‐ the Big Five‐, i.e., African elephant ( Loxodonta africana ), rhinoceros ( Diceros bicornis , Ceratotherius simum ), lion ( Panthera leo ), African buffalo ( Syncerus caffer ), and leopard ( Panthera pardus ).…”
Section: Figurementioning
confidence: 99%
“…Eyster, Naidoo, & Chan (2022) importantly suggest that the negative association found in their study between tourists' visits and nearby human population may imply that revenues from ecotourism could favor the displacement of people and the conservation of landscape types which may not be envisioned or desired by locals. In protected areas, ecotourism imaginaries can drive environmental change by influencing normative value judgments on how landscapes should look like, which species are considered of value, and thus worth conserving, and for whom.…”
mentioning
confidence: 91%
“…Eyster, Naidoo, & Chan (2022) found that beyond charismatic megafauna, areas with high bird diversity may also attract more visitors. Birdwatching is a growing niche in nature‐based tourism attracting bird enthusiasts to diverse locations worldwide.…”
mentioning
confidence: 99%
See 2 more Smart Citations